The Mystery Box Game in Improving Dental Health Knowledge in Elementary School - Ansyori, Bros Al; Purnama, Tedi; Rikawarastuti, Rikawarastuti; Kristianto, Jusuf; Emini, Emini (Journal Center of Excellent : Health Assistive Technology, 2025)
Dental and oral health is an important aspect in maintaining overall body health. Based on the Indonesian Health Survey (SKI), West Java province has a prevalence of caries at the age of 10-14 years reaching 48%. Low knowledge about dental and oral hygiene is the main cause of increased risk of dental disease. One effort to help improve dental and oral health is providing dental health education. Objective: Knowing the mystery game box in increasing dental health knowledge among fifth grade students at SDN Cinere 02 Depok in 2025. Method: This research was carried out using the method quasi-experiment with one group pretest and post-test design. This research was conducted at SDN Cinere 02 Depok. The sampling technique uses total sampling, totalling 30 students. Independent variable: game dental mystery box and dependent variable: students' level of dental health knowledge. The instruments used were questionnaires and game media dental mystery box. Results: This research shows the average value of dental health knowledge before playing with the game dental mystery box which is 70.47 and after playing the game dental mystery box namely 96.67. Conclusion: Games dental mystery box effectively increasing dental health knowledge in fifth grade students at SDN Cinere 02 Depok.